Phytochemical Analysis and Antimicrobial Activity of Methanolic and Aqueous Stem Extracts of Guiera senegalensis Against Bacterial Pathogens - Tyohemba, Samuel Terhide; Suwaiba, Ladan Muhammad; Ndukwe, Nelson Nwachukwu; Adoyi, Michael Paul; Catherine O., Attah; Asiya, Mamoon; Mbahi, Asugu Mary (FUDMA Journal of Sciences, 2025)
With the growing resistance of pathogens to conventional antibiotics, there is an increasinginterest in exploring alternative treatments derived from medicinal plants, particularly those richin bioactive compounds. Guiera senegalensis, a medicinal shrub native to West and CentralAfrica, has traditionally been used to treat gastrointestinal disorders, fever, and rheumatism. Thisstudy aimed to investigate the presence of bioactive compounds and antimicrobial properties ofthe stem extract of G. senegalensis, with a particular focus on its efficacy against bacterialinfections.Phytochemicals were extracted through cold maceration using methanol and distilledwater as solvents. The antimicrobial effects of the extracts on clinical isolates of Salmonellatyphi, Escherichia coli, and Pseudomonas aeruginosa were evaluated via the agar disc diffusionmethod.Phytochemical analysis of both the methanol and aqueous extracts revealed the presenceof alkaloids, flavonoids, tannins, and saponins. The methanol extract exhibited higherconcentrations of flavonoids, tannins, and saponins, whereas the aqueous extract contained morealkaloids. Antimicrobial assays demonstrated that both extracts inhibited all tested bacterialstrains, with the methanol extract demonstrating significant efficacy against E. coli, with aninhibition zone of 25 mm at 500 µg/mL. The minimum inhibitory concentration (MIC) valuesranged from 6.25 to 500 µg/mL, indicating that these extracts may serve as alternative treatmentsfor infections, particularly those resistant to antibiotics.These findings substantiate thetherapeutic potential of G. senegalensis as a source of antimicrobial agents, corroborating itstraditional use in treating infectious diseases.
Keywords: Aqueous extract; antimicrobial properties; Guiera senegalensis; methanol extract; phytochemicals